2010
DOI: 10.1016/j.jtcvs.2009.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Comparable patencies of the radial artery and right internal thoracic artery or saphenous vein beyond 5 years: Results from the Radial Artery Patency and Clinical Outcomes trial

Abstract: At mean 5-year angiography in largely asymptomatic patients, the selection of arterial or venous conduit for the second graft has not significantly affected patency. This finding offers surgeons, for now, enhanced flexibility in planning revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
88
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 17 publications
5
88
0
4
Order By: Relevance
“…12 In a recent randomised controlled trial conducted at 11 Veterans Affairs medical centres in United States undergoing first-time elective CABG, 13 the 1-year graft patency of the radial artery conduits was not significantly greater than venous grafts. In fact, the 7-year patency rates for the vein grafts were also similar to the radial artery conduits in a randomised Australian trial 11 as well as in a retrospective French series with 20-year follow-up. 14 The relevance of vein graft failure, therefore, should not be overlooked.…”
Section: Clinical Use Of Autologous Saphenous Veinsupporting
confidence: 52%
See 2 more Smart Citations
“…12 In a recent randomised controlled trial conducted at 11 Veterans Affairs medical centres in United States undergoing first-time elective CABG, 13 the 1-year graft patency of the radial artery conduits was not significantly greater than venous grafts. In fact, the 7-year patency rates for the vein grafts were also similar to the radial artery conduits in a randomised Australian trial 11 as well as in a retrospective French series with 20-year follow-up. 14 The relevance of vein graft failure, therefore, should not be overlooked.…”
Section: Clinical Use Of Autologous Saphenous Veinsupporting
confidence: 52%
“…Furthermore, distal coronary 'run-off' can affect the long-term vein graft patency. [10][11][12] As the severity of disease in the native coronary recipient artery increases, distal run-off may reduce. In the Radial Artery Patency and Clinical Outcomes (RAPCO) trial, saphenous vein graft patency (measured by the protocol-directed angiograms) was demonstrated in 80% of subjects at 9 years.…”
Section: Clinical Use Of Autologous Saphenous Veinmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome (RAPCO) [3] which randomized 196 patients to the RITA and 193 patients to the RA. At midterm follow-up no significant differences in terms of angiographic patency and clinical outcome were found.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, whether the use of the right internal thoracic artery (RITA) confers a survival advantage when compared to the radial artery (RA) still needs to be determined [3]. To date, only a single randomized controlled trial (RCT) [3] has been published in the literature, largely underpowered to detect any difference in long term survival between RITA and RA groups. Several observational studies comparing RITA versus RA have been reported with conflicting findings [5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%